2011
DOI: 10.5539/jas.v3n2p149
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Salicylate Affects the Quality of Hayward Kiwifruits during Storage at Low Temperature

Abstract: Hayward kiwifruit were treated with methyl salicylate (MeSA) at different concentrations (0, 8, 16, 24, 32 µL.L -1 ), then stored at 0.5 ºC and 90% RH for 5 months to investigate postharvest quality and ripening behavior. MeSA treatments, especially at 32 µL.L -1 concentrations, were highly effective in reducing ethylene production, fungal decay, APX and CAT activity, weight loss and total soluble solids (TSS) in Hayward kiwifruit, as well as ascorbic acid (AA) and flesh firmness loss compared with that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(31 reference statements)
3
4
0
Order By: Relevance
“…Our results are in agreement with Soleimani Aghdam et al (2011) who found that MeSA treatment significantly affected pH and pH of kiwifruit fruit juice increased after 3 months of storage but then decreased to end of storage. The fluctuations of pH might be due to the variations in TA or temperature of storage and the decline of acidity is attributed due to increased activity of citric acid content may be due to their conversion into sugars and further utilization in metabolic process during storage (Rathore et al, 2007).…”
Section: Phsupporting
confidence: 83%
See 4 more Smart Citations
“…Our results are in agreement with Soleimani Aghdam et al (2011) who found that MeSA treatment significantly affected pH and pH of kiwifruit fruit juice increased after 3 months of storage but then decreased to end of storage. The fluctuations of pH might be due to the variations in TA or temperature of storage and the decline of acidity is attributed due to increased activity of citric acid content may be due to their conversion into sugars and further utilization in metabolic process during storage (Rathore et al, 2007).…”
Section: Phsupporting
confidence: 83%
“…The application of SA can increase vitamin C content and then decrease antioxidant in strawberry fruit (Jing-Hua et al, 2008). Soleimani Aghdam et al (2011) found that MeSA treatment maintained significantly ascorbic acid content of the kiwifruit during storage and there was a positive correlation between MeSA concentration and fruit ascorbic acid content that are in agreement with our results. Hung et al (2007) suggested that high ascorbate (AA) contents in the pulp of pretreated fruit with SA may result from an acceleration of biosynthetic pathways or a decrease in catabolism through an accumulation of dehydroascorbate (DHAA).…”
Section: Phsupporting
confidence: 82%
See 3 more Smart Citations